Kajian Potensi Ekowisata Hutan Mata Kucing sebagai Daya Tarik Wisata Alam di Kota Batam - Chelsea, Chelsea; Mulyadi, Tirta; Silitonga, Frangky (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to analyze the condition of the Mata Kucing Tourist Forest as one of the natural tourist attractions in Batam City, Indonesia. A descriptive qualitative analysis approach and a SWOT analysis tool, this research evaluates the internal and external factors that influence the management and development of the Mata Kucing Tourism Forest area. Data was collected through interviews, questionnaires and observations. The research results show that the area has strengths in its strategic location, adequate facilities and attractive natural environment. However, several weaknesses such as lack of promotion and sufficient supervision are challenges. Opportunities for development include the use of public transport, affordability and animal diversity. The threat is mainly related to the prices of food and drinks in tourist forests. Based on the SWOT analysis, a development strategy is proposed to exploit internal strengths and external opportunities while overcoming internal weaknesses and anticipating external threats.